Psicopedagogical basis for habilities acquisition. An example of its application through diagnose hability - Luis Alberto Corona Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
The acquisition of abilities constitutes one of the most important objectives in the teaching -educational process; its correct formation is necessary, for the determination of those actions and operations that the student should assimilate to dominate them. This article seeks to familiarize the professors with some essential concepts: activity, actions, operations, functional invariants; whose understanding is indispensable for the work directed to the formation of abilities. The application of these concepts, is exemplified by means of a system of actions and operations for the formation of the ability to diagnose.